Asian Derivative Markets: Research Issues - M., Shamsher; H., Taufiq (Universiti Utara Malaysia, 2007)
Theory suggests that the introduction of derivative market in a market with spot trading completes the market-based price discovery process.There are 19 derivative markets in Asia. Derivative trades in such markets help to hedge away the risk of price changes in the spot markets at very low costs. Commodity futures instruments are also needed to hedge away price changes in real sector just as financial futures does this function for the financial sector. In this paper, we examine the current status of selected commodity and financial derivative markets in Asia.It suggests that the more industrial/advanced economies have developed liquid commodities markets, and few of them have also developed active financial derivative markets. But for most of the 19 or so emerging markets in Asia, the development of derivative markets is still at an early stage.